(For)Bearing the costs of reckless lending: examining the response to the Irish mortgage arrears crisis. Issue 3 (2nd July 2016) - Waldron, Richard; Redmond, Declan
Abstract : Compared to the extensive assistance afforded to Ireland's banks since 2008, interventions to assist troubled mortgagors have been limited, with Government and the banks strongly resisting debt write-downs in favour of a policy of mortgage forbearance. Forbearance involves restructuring a debt's contractual terms to ease a debtor's repayment schedule. In practice, forbearance has been a strategy of 'extend and pretend' where lenders have been slow to offer restructurings or have relied on temporary interventions that impose minimal costs upon them. Forbearance benefited lenders by negating the pressure to enforce possession of devalued property, while ensuring borrowers remain solely responsible for outstanding debts. Despite the emphasis on forbearance, few studies have examined borrowers' experiences of forbearance, particularly their experience of communicating their difficulties with their lenders. This paper first utilises national data to examine forbearance as a strategic response by the Irish authorities to the mortgage arrears crisis. Second, mortgage-stressed borrowers' experiences of forbearance are examined using data drawn from a survey ( n = 433) of mortgagors which dealt specifically with mortgage payment issues following the crash. The article documents a shift in lenders' arrears management strategies from 2013, with an increased emphasis on longer term restructurings but also an increasing appetite for repossession.